2013
DOI: 10.1111/hex.12040
|View full text |Cite
|
Sign up to set email alerts
|

Parents' experiences of living with a child with a long‐term condition: a rapid structured review of the literature

Abstract: Background Living with a child with a long-term condition can result in challenges above usual parenting because of illnessspecific demands. A critical evaluation of research exploring parents' experiences of living with a child with a long-term condition is timely because international health policy advocates that patients with long-term conditions become active collaborators in care decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
201
2
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(228 citation statements)
references
References 65 publications
13
201
2
12
Order By: Relevance
“…Actively involving parents in care decisions, and children and young people as appropriate, is particularly salient in the context of long-term conditions where the day-to-day management of care becomes primarily the responsibility of the family. Evidence suggests that care-giving such as providing medical and nursing interventions above usual parenting tasks is a significant feature of living with a child with a long-term condition for both fathers and mothers (Cashin, Small & Solberg, 2008;Smith, Cheater & Bekker, 2013a;Wennick & Hallström, 2007). In order to manage their child's condition, parents need to; gain knowledge of the condition and treatments (Bailing & McCubin 2001;Knafl, Deatrick, Knafl, Gallo, et al, 2013, Nuutila & Salanterä, 2006; learn how to identify and respond to illness symptoms in their child (Smith, Cheater, Bekker & Chatwin, 2013b;Wennick & Hallström, 2007); and develop effective relationships with health professionals (Dickinson, Smythe, & Spence, 2006;Swallow & Jacoby, 2001;Swallow, Lambert, Santacroce, Macfadyen, 2011;Swallow, Macfadyen, Santacroce & Lambert, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Actively involving parents in care decisions, and children and young people as appropriate, is particularly salient in the context of long-term conditions where the day-to-day management of care becomes primarily the responsibility of the family. Evidence suggests that care-giving such as providing medical and nursing interventions above usual parenting tasks is a significant feature of living with a child with a long-term condition for both fathers and mothers (Cashin, Small & Solberg, 2008;Smith, Cheater & Bekker, 2013a;Wennick & Hallström, 2007). In order to manage their child's condition, parents need to; gain knowledge of the condition and treatments (Bailing & McCubin 2001;Knafl, Deatrick, Knafl, Gallo, et al, 2013, Nuutila & Salanterä, 2006; learn how to identify and respond to illness symptoms in their child (Smith, Cheater, Bekker & Chatwin, 2013b;Wennick & Hallström, 2007); and develop effective relationships with health professionals (Dickinson, Smythe, & Spence, 2006;Swallow & Jacoby, 2001;Swallow, Lambert, Santacroce, Macfadyen, 2011;Swallow, Macfadyen, Santacroce & Lambert, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kubler-Ross believed that these steps may not necessarily come in the above order and that there is a possibility that affected individuals may not experience all five stages. A review of 34 studies conducted by Smith et al (2013) focused on parental experiences when having a child diagnosed with a long-term medical condition found that parents experienced several emotions such as shock, disbelief and anxiety of having a child diagnosed with a chronic illness. These grief reactions often disappeared if parents accepted the reality otherwise parents may refuse to believe their child's situation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…These grief reactions often disappeared if parents accepted the reality otherwise parents may refuse to believe their child's situation. Therefore, parents expressed various emotional reactions such as anger, blame and/or guilt (Smith et al, 2013). The grief and loss paradigm assumed that parents undergo (i.e.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Os pais experimentam uma gama de emoções, precisando incorporar saberes e práticas desconhecidas em seu cotidiano, e enfrentam cuidados desafiadores para o atendimento das atividades diárias de seu filho. O ambiente domiciliar passa por adaptações com presença de novos equipamentos para a sobrevida dessa criança, que se somam aos brinquedos e pertences, cujo valor é inestimável para o seu desenvolvimento 8,23 .…”
unclassified